2007
DOI: 10.1002/dvdy.21299
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress induced by tunicamycin disables germ layer formation in Xenopus laevis embryos

Abstract: Maintenance of endoplasmic reticulum (ER) homeostasis is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…This response is orchestrated by several sensing mechanisms and finally transmitted to the nucleus in the form of activated transcription factors Xbp1 and members of the ATF/Creb family (Calfon et al, 2002;Haze et al, 1999;Kondo et al, 2005;Kondo et al, 2007;Yoshida et al, 2001). Xbp1 has previously been identified in Xenopus embryos and shown to have a role in regulating BMP signaling, in mesoderm formation, and in the response of the embryo to ER stress (Cao et al, 2006;Yuan et al, 2007;Yuan et al, 2008;Zhao et al, 2003). We find that xbp1 and at least one Creb family gene, creb3l2, are preferentially expressed in the notochord and are required for notochord differentiation.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…This response is orchestrated by several sensing mechanisms and finally transmitted to the nucleus in the form of activated transcription factors Xbp1 and members of the ATF/Creb family (Calfon et al, 2002;Haze et al, 1999;Kondo et al, 2005;Kondo et al, 2007;Yoshida et al, 2001). Xbp1 has previously been identified in Xenopus embryos and shown to have a role in regulating BMP signaling, in mesoderm formation, and in the response of the embryo to ER stress (Cao et al, 2006;Yuan et al, 2007;Yuan et al, 2008;Zhao et al, 2003). We find that xbp1 and at least one Creb family gene, creb3l2, are preferentially expressed in the notochord and are required for notochord differentiation.…”
Section: Introductionmentioning
confidence: 60%
“…Thus the inhibition of expression of Xbp1 or Creb3l2 leads to an impairment of notochord morphology by tailbud stages of embryogenesis. Manipulation of Xbp1 and Creb3l2 protein levels affects the expression of some secretory protein genes Xbp1 is known to have a role in Xenopus embryogenesis (Cao et al, 2006;Yuan et al, 2008;Zhao et al, 2003) and to be involved in the response to ER stress (Yuan et al, 2007). We tested whether inhibition of Xbp1 or Creb3l2 affects the expression of secretory pathway genes at early and later stages of notochord differentiation.…”
Section: Requirement For Xbp1 and Creb3l2 In Notochord Developmentmentioning
confidence: 99%
“…TM is the inducer of UPR, and it was reported that TM induced severe ER stress with an apparent increase in XBP1 splicing and caused serious developmental defects in Xenopus [19]. We speculated that, if XBP1 splicing is repressed, the developmental defects could be rescued.…”
Section: Resultsmentioning
confidence: 95%
“…In parallel, ODC was amplified to confirm equal amounts and integrity of different RNA preparations. Real time RT-PCR was performed and primers for chop were as described previously[19].…”
Section: Methodsmentioning
confidence: 99%
“…TUNI triggers stress by inhibiting N-linked glycosylation of newly synthesized proteins in the ER [41]. Glycosylation is essential for controlling both the processing and quality of protein folding.…”
Section: Tuni and Ersmentioning
confidence: 99%